Venoarterial Extracorporeal MembraneOxygenation in Septic Shock and/or Sepsis-induced Cardiomyopathy: A Systematic Review of Fifteen Studies - Ans Alamami (14777233) (2025)
Objective(s) To evaluate survival outcomes and identify candidate profiles for venoarterial extracorporeal membrane oxygenation in adult patients with sepsis-induced cardiomyopathy. Design The authors systematically searched PubMed, Embase, and Google Scholar up to October 22, 2024, for English-language studies investigating venoarterial extracorporeal membrane oxygenation in adult patients with septic shock and/or sepsis-induced cardiomyopathy. Two reviewers independently screened studies, assessed quality, and extracted data on demographics, illness severity, and survival. Setting Studies were conducted in intensive care units across multiple international centers. Participants A total of 15 studies, including 1,110 adult patients with septic shock and/or septic cardiomyopathy who underwent extracorporeal membrane oxygenation support, were identified. Interventions Venoarterial extracorporeal membrane oxygenation was implemented as a salvage therapy for refractory septic shock and/or sepsis-induced cardiomyopathy. Measurements and Main Results The primary outcome was survival to hospital discharge. Secondary data included age, mean arterial pressure, arterial pH, lactate level, PaO₂/FiO₂ ratio, ejection fraction, inotrope score, and Sequential Organ Failure Assessment (SOFA) score. The pooled survival rate was 42%. At venoarterial extracorporeal membrane oxygenation initiation, patients exhibited severe hemodynamic instability: mean age 52 ± 6 years; mean arterial pressure 62 ± 8 mmHg; pH 7.20 ± 0.07; lactate 9 ± 6 mmol/L; PaO₂/FiO₂ 85 ± 20; ejection fraction 33% ± 15; inotrope score 122 ± 99 μg/kg/min; SOFA score 15 ± 3. Conclusions Venoarterial extracorporeal membrane oxygenation may provide meaningful survival benefits in carefully selected patients with severe, refractory septic shock and/or sepsis-induced cardiomyopathy. Given the observational nature and the heterogeneity of the included studies, these findings should be interpreted with caution. Further prospective trials are needed to refine patient selection and optimize outcomes. Other Information Published in: Journal of Cardiothoracic and Vascular Anesthesia License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1053/j.jvca.2025.09.237